Incidence of burnout among PLM-PT Interns Batch 2001-2002 and its effect on their clinical performance - Abad, Myra B.; Jugo, Mary Joan R.; Mendiola, Michelle Paula M.; Saligumba, Yehlen Francis R. and Zulueta, Rowena T. 4 0 16; 5 (2002)
u
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila, 2002;College of Physical Therapy, Bachelor of Science in Physical Therapy
Keywords: 2 -- 0; 6; 20; 20; 2